Chemical synthesis of zinc oxide nanoparticles and their evaluation in Lactuca sativa seedlings - Galindo-Guzmán, Alma Patricia; Fortis-Hernández, Manuel; De La Rosa-Reta, Claudia Verónica; Zermeño-González, Héctor; Galindo-Guzmán, Magdalena (Revista Mexicana de Ciencias Agrícolas, 2022)
There are currently studies on the different effects of nanomaterials in agriculture to improve crop germination and productivity, in order to ensure economic sustainability and the efficient use of production resources in agriculture. The ZnO nanoparticles applied in this study were synthesized by a chemical precipitation method and their characterization was performed by XRD, SEM, UV-visible spectroscopy and FTIR. The effect on the germination of lettuce (Lactuca sativa) seeds was determined by means of a completely randomized design with five ZnO-NPs treatments and a control treatment each with four repetitions. Physiological indices were measured, chlorophyll and carotenoid contents, and phenolic compound content in lettuce seedlings were quantified. The results indicate that applying doses of 50 mg L-1 ZnO-NPs, higher values of germination percentage (36.97%), fresh weight of plumule (23.91%), fresh weight of radicle (63.25%) and radicle length (50.58%) were achieved compared to the control groups. Likewise, the total phenol content increased (207.9%). Doses greater than 125 mg L-1 ZnO-NPs decrease the chlorophyll content, causing phytotoxic effects on L. sativa seedlings. As for the carotenoid content, the best treatment was 100 mg L-1 ZnO-NPs. The use of ZnO-NPs synthesized through a chemical precipitation method is a good alternative to be used as inducers in the biosynthesis of bioactive compounds in lettuce seedlings.